Some Pathogenic Bacteria of Livestock Origin as a Cause of Foodborne Diseases - Anni Kusumaningsih (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2010)
Food are essentialy required for cell metabolism in human physiologyc. Food should be free from biological, chemical, and physical contamination and also hazardous substances. All of them are able to disrupt physiological homeostatis resulting disorder or diseases. Diseases resulted by those contaminant are called food borne disease. One of the important contaminants is biological contaminant especially pathogenic bacterias. Some pathogenic bacteria such as Salmonella spp., Escherichia coli, Bacillus anthracis, Clostridium spp., Listeria monocytogenes, Campylobacter spp., Vibrio cholerae, Enterobacter sakazakii, Shigella, are able to cause symptomatic diseases. Overall, the general symptoms of the diseases due to pathogenic bacterial infection are gastric pain, nausea, vomit, headache, loss of appetite, fever, and also dehydration. Key words: Pathogenic bacteria, foodborne diseases, food